COMPARATIVE ANALYSIS OF MAGICAL JEWELLERY AND ORNAMENTS IN ENGLISH AND UZBEK FAIRY TALES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The existence of magical objects in fairy tales makes them more impressive. There are different types of magical items in both English and Uzbek fairy tales. The article discusses the similarities and divergencies concerning magical objects in the English and Uzbek fairy tales, existence of magical jewellery and ornaments and their functions in the fairy tales of two different nations. The author also mentions about the genesis of magical items and their connection with the culture, traditions and religious beliefs of the nations.